(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Integrity and Freedom of Conscience in the Romanian Rural Environment In the present study we make first of all an objective analysis of the Romanian rural environment from the point of view of transmission of the information, in the context of integrity and freedom of conscience. For example, we offer, unfortunately, two cases of violation of freedom of conscience in two rural localities, Urlați and Puchenii Moșneni, Prahova County. The stages in creating a climate equidistant for religious freedom in rural areas is another point of research, followed by the factors of responsibility needed to promote religious freedom in rural areas. In the last part of the study we list some programs meant to promote the universal human right to freedom of conscience in Romanian communes and villages.